2012
DOI: 10.6061/clinics/2012(01)04
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to AIDS among the elderly in an urban center in central Brazil

Abstract: OBJECTIVE:As the world population ages with an improved quality of life and sexual longevity, the prevalence of AIDS is rising among the elderly. The purpose of this study was to estimate the vulnerability to AIDS among individuals attending senior community centers in Campo Grande, Mato Grosso do Sul, Brazil.METHOD:This descriptive, exploratory investigation included 329 subjects selected in a probabilistic manner. Individuals with scores on the Mini-Mental State Examination indicating cognitive impairment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
(50 reference statements)
0
13
0
8
Order By: Relevance
“…Our cohort is predominantly composed of medical indigent patients, thus our study adds an additional dimension of vulnerability in the population studied which is most likely affected by disparities in health care delivery and access. 6,7,15 It is recognized that despite the elderly being the new at-risk group for HIV, little research is devoted to addressing the specific issues affecting diagnosis, prevention and treatment of AIDS in this specific cohort. 16,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cohort is predominantly composed of medical indigent patients, thus our study adds an additional dimension of vulnerability in the population studied which is most likely affected by disparities in health care delivery and access. 6,7,15 It is recognized that despite the elderly being the new at-risk group for HIV, little research is devoted to addressing the specific issues affecting diagnosis, prevention and treatment of AIDS in this specific cohort. 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…5,15,21,28,30 Our studies introduce the additional variable of BMI as an element that may be synergistically detrimental in the natural history of HIV infection in this cohort of patients. 1,29,31 …”
Section: Discussionmentioning
confidence: 99%
“…It is observed that what happens is fragmented care because many actions, such as the prevention of STD/AIDS, the approach to discuss sexuality, and the HIV serology request are not being performed (3,14,22) . However, the perception that health professionals have about elderly sexuality is directly reflected to the way they approach this subject with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although not recognized as a risk group for STI, sexually active older people can be particularly vulnerable to these diseases because of behavioral aspects such as condom usage. Driemeier et al 5 , analyzing elderly vulnerability to STI in 2009, found that only 14% of respondents reported use of condoms.…”
Section: Introductionmentioning
confidence: 99%